Peculiarities of the situation and problematic issues of the use of border units in the context of a stabilization operation - Kit, Valeriy; Beka, Olexandr; Lukovskyi, Ivan (Social Development and Security, 2024)
Purpose: to summarize the peculiarities of the situation on the northeastern section of the state border in the context of the stabilization operation and problematic issues of countering sabotage and reconnaissance groups of the enemy. Method: system analysis, generalization, synthesis. Findings: an analysis of the experience of using border units to counteract enemy sabotage and reconnaissance groups on the Russian-Ukrainian border. Theoretical implications: includes several key aspects that are important for understanding and solving current problems, namely, analysis of stabilization operations, study of the peculiarities of the work of border units, identification of problematic issues, development of recommendations for the head of the border unit and increase of the level of security and control. Practical value of the study: includes a number of aspects that can be useful for practical activities in the field of security and management, namely, increasing the effectiveness of crisis response, improving cooperation and coordination of activities, ensuring the safety of citizens and territory, as well as the development of technological solutions. Originality: it studies specific aspects of the work of border units in the context of stabilization operations, which is important in the context of ensuring security and effective management of border areas in conditions of instability. Paper type: theoretical.